A rapid evidence review on the effectiveness of institutional health partnerships. Issue 1 (December 2015) - Kelly, Ema; Doyle, Vicki; Weakliam, David; Schönemann, Yvonne
Abstract Background Institutional Health Partnerships are long-term, institution to institution partnerships between high income and low and middle income countries which seek to build capacity and strengthen health institutions in order to improve health service delivery and outcomes. Funding for Institutional Health Partnerships has increased in recent years. This paper outlines a rapid evidence review on the effectiveness of this modality. Methods A rapid evidence review of published and grey literature was conducted. Content relating to the effectiveness of working in partnership and methods and frameworks used were extracted and analysed. The results of this analysis were used to structure a discussion regarding the next steps to strengthen the evidence base for the effectiveness of institutional health partnerships. Results The evidence review, including citation mapping, returned 27 published papers and 17 grey literature documents that met all of the inclusion criteria. Most of the literature did not meet the high standards of formal academic rigour and there was no original research amongst this literature that specifically addressed the effectiveness of institutional health partnerships. This was not surprising given institutional health partnerships do not lend themselves easily to case control studies and randomised control trials due to their high level of diversity and operation in complex social systems. There was, however, a body of practice based knowledge and experience. Conclusions Evidence for the effectiveness of Institutional Health Partnerships is thin both in terms of quantity and academic rigour. There is a need to better define and differentiate Institutional Health Partnerships in order to measure and compare effectiveness across such a diverse group. Effectiveness needs to be measured at the level of individual partnerships, the bodies that facilitate partnership programmes and the level of health service delivery. There is a need to develop indicators and frameworks that specifically address the benefits and values of partnership working and how these relate to effectiveness. These indicators need to be content neutral of specific interventions which are already measured through routine project monitoring and evaluation. This will allow the development of methodological pathways to assess the effectiveness of institutional health partnerships. Until more primary research is conducted or published there is little benefit in further systematic reviews.